Sexual dimorphism and geographic variation of the skull of the fishing bat Noctilio leporinus (Chiroptera: Noctilionidae) in Mexico - Sandra Milena Ospina-Garcés; Livia León-Paniagua (Revista Mexicana de Biodiversidad)
The fishing bat Noctilio leporinus Linnaeus, 1758, represents a complex of subspecies with a discontinuous lowland distribution in Central, South America and the Caribbean. Although Mexican populations are currently included in the subspecies N. l. mastivus, the morphological variation in these groups has been poorly studied and only the body size differences with other subspecies have been documented. In addition, sex differences in cranial morphology for this complex of subspecies have been identified previously. To determine whether there are geographic differences between 2 isolated Mexican populations of N. l. mastivus and quantify the cranial sexual dimorphism in this subspecies, we performed geometric morphometric analyses of 2 dimensional landmark configurations describing cranial shapes. Our results support significant shape differences between the Pacific coast (west) and Gulf of Mexico-Yucatán Peninsula (east) populations, but no differences in cranial size were found. There were differences between sexes in the size and shape of the sagittal crest, in both populations, and these results suggest a continuous trend of development of this character in males, which imply functional differences in masticatory function between sexes. Morphological differences between populations could be related to genetic isolation and may be accentuated by differences in habitat structure between the dry (west) and humid (east) slopes of the Mexican mountains.